2010
DOI: 10.1016/j.tranpol.2010.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Examining individuals preferences for hybrid electric and alternatively fuelled vehicles

Abstract: The survey also contained a number of stated preference experiments which were designed to ascertain what factors influence individuals' decisions when purchasing their new car. The results showed that respondents did not rate green house gas emissions or VRT as crucial attributes when purchasing a new vehicle. The vehicle attributes that respondents rated most highly were reliability, automobile safety, fuel costs, and the cost price. The majority of respondents agreed that HEVs and AFVs are better for the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(95 citation statements)
references
References 6 publications
6
87
2
Order By: Relevance
“…Second, research from the 80s and 90s mainly focused on the potential demand for battery EVs [13,14,24,27,38,39,54,55,79,90], while studies from the late 90s and 2000s rather address a mix of AFVs including EVs, LPG, CNG or methanol [21][22][23]33,34,42,81,87]. In line with technological developments, recent research also concentrates on HEVs [3,10,26,29,31,32,45,49,53,72], PHEVs [ 9 , 11], bi ofuels [51,68,69,80,89,91], hydrogen [2,66,74,76,86] and HFCVs [46,61,62,65]. Finally, most literature has been published in America.…”
Section: Evaluation Of the Retrieved Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Second, research from the 80s and 90s mainly focused on the potential demand for battery EVs [13,14,24,27,38,39,54,55,79,90], while studies from the late 90s and 2000s rather address a mix of AFVs including EVs, LPG, CNG or methanol [21][22][23]33,34,42,81,87]. In line with technological developments, recent research also concentrates on HEVs [3,10,26,29,31,32,45,49,53,72], PHEVs [ 9 , 11], bi ofuels [51,68,69,80,89,91], hydrogen [2,66,74,76,86] and HFCVs [46,61,62,65]. Finally, most literature has been published in America.…”
Section: Evaluation Of the Retrieved Datamentioning
confidence: 99%
“…Later research also included HEVs, PHEVs and HFCVs in the vehicle choice experiments. These reviewed CM studies reveal that the most critical factors for the adoption of AFVs are price characteristics (e.g., purchase price, fuel costs) [3,26,29,33,72,79], followed by performance and convenience attributes (e.g., driving range, recharging times, fuel availability) [13,14,21,24,27,29,33,42,72,79]. Although people express a willingness to pay for reduced emission levels [21,23,87], environmental benefits are consistently found to be of minor importance compared to these attributes [26,27,34,72].…”
Section: Preference Valuation Studiesmentioning
confidence: 99%
“…There is evidence to suggest that fuel economy, government incentives, environmental concerns, and general interest in technological innovations are influential in driving vehicle purchasing decisions (Caulfield et al, 2010;Ozaki and Sevastyanova, 2011). Although Diamond (2009) finds that gasoline prices are a much stronger determinant of hybrid vehicle adoption than policy incentives.…”
Section: Introductionmentioning
confidence: 99%
“…More than 51% of residents consider the higher BEV price as the main obstacle for purchase. Caulfield et al [34], and Caperello and Kurani [35] showed that BEV purchase and operating costs were the most important factors for residents. Li [36] proposed that the key factors restricting China's BEVs industry was still the high cost of BEV purchase, coupled with low market acceptance and government subsidies.…”
Section: Attribute Factors That Hinder Bev Purchase Intentionmentioning
confidence: 99%